THE IMPACT OF MODERATE PHYSICAL LOADS ON CENTRAL HEMODYNAMICS OF PHYSICAL THERAPY STUDENTS - Berhtraum, D.I.; Vovkanych, L.S.; Svyshch, Y.S.; Dukh, T.I.; Dunets-Lesko, A.V. (World of Medicine and Biology, 2024)
We aimed to study the impact of non-professional sports training on central hemodynamics in physiotherapy students aged 17–18 years. Participants were divided into low-active (44 male, 27 female) and physically active groups (19 male, 12 female). We measured heart rate and central hemodynamics parameters. Non-professional sports activities significantly influenced hemodynamics, leading to bradycardia, a tendency towards lower systolic blood pressure, a decreased cardiac index, and an increase in individuals with a hypokinetic hemodynamic type and inotropic cardioregulation. These activities also decreased Robinson index values, increased cardiovascular system reserve capabilities, elevated the frequency of vagotonia at rest, and improved physical working capacity and maximal oxygen consumption in both genders. Our findings suggest that self-determined non-professional sports activities have significant potential for improving the health and fitness of physiotherapy students.
Keywords: systolic volume; cardiac index; Robinson index; Kerdo index; adaptotropic index